1998
DOI: 10.1016/s0014-5793(98)01523-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of Spodoptera frugiperda (Sf9) and Trichoplusia ni (Tn) insect cells used for baculovirus infection

Abstract: The lipid composition of two different insect cell lines from Spodoptera frugiperda (Sf9) and Trichoplusia ni (Tn) which are established cell lines for infection with recombinant baculovirus was analyzed by high-performance liquid chromatography and gas-liquid chromatography. The major phospholipids found were phosphatidylcholine and phosphatidylethanolamine, the major mono-unsaturated fatty acids were oleic acid and palmitoleic acid, the major saturated fatty acid was stearic acid. The cholesterol to phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
104
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 20 publications
15
104
1
Order By: Relevance
“…Our data largely agree with published studies analyzing the lipid composition of insect cell membranes (11), in particular SF9 cells (12), especially regarding limited amounts of cholesterol as well as for their high PE content. In contrast, we found that SF9 similarly to HEK 293T cells contain all major PL species, notably PG, PS, and SM, which was described for Drosoph- (13).…”
Section: Lipidic Composition Of Insect and Mammaliansupporting
confidence: 92%
“…Our data largely agree with published studies analyzing the lipid composition of insect cell membranes (11), in particular SF9 cells (12), especially regarding limited amounts of cholesterol as well as for their high PE content. In contrast, we found that SF9 similarly to HEK 293T cells contain all major PL species, notably PG, PS, and SM, which was described for Drosoph- (13).…”
Section: Lipidic Composition Of Insect and Mammaliansupporting
confidence: 92%
“…Thus, viral envelopes are likely to contain more PE than PS. With PE content in insect cells being even higher (as much as 46-58%) (44)(45)(46)(47)(48), it is not surprising that arboviruses, such as flavi-and alphaviruses, evolved to use PE-binding receptors like TIM1 with high efficiency (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…This observation has been explained in terms of an altered permeability of these cells combined with the ability of ribotoxins to interact with acid phospholipid-containing membranes (Gasset et al, 1989(Gasset et al, , 1990Herrero-Galán et al, 2008, 2012bMartínez-Ruiz et al, 2001;Olmo et al, 2001). Insect cells have a different plasma membrane composition from mammalian cells due to their higher content of phosphatidylcholine, phosphatidylethanolamine and phosphatidylinositol and a significant lower cholesterol/phospholipid ratio (Marheineke et al, 1998). Therefore insect plasma membranes are thinner and probably more fluid than those in mammalian cells being better candidates as targets for ribotoxins.…”
Section: Discussionmentioning
confidence: 99%